2012
DOI: 10.1002/nur.21503
|View full text |Cite
|
Sign up to set email alerts
|

Nurse reported quality of care: A measure of hospital quality

Abstract: As the primary providers of round-the-clock bedside care, nurses are well positioned to report on hospital quality of care. Researchers have not examined how nurses’ reports of quality correspond with standard process or outcomes measures of quality. We assess the validity of evaluating hospital quality by aggregating hospital nurses’ responses to a single item that asks them to report on quality of care. We found that a 10% increment in the proportion of nurses reporting excellent quality of care was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
202
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(216 citation statements)
references
References 37 publications
9
202
0
5
Order By: Relevance
“…Consequently, nurses are frequently referred to as reliable and valid informants of quality of care. Empirical evidence has shown that nurse-reported quality of care is an indicator of hospital performance comparable to objective indicators of quality such as mortality and failure-to-rescue (McHugh and Stimpfel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nurses are frequently referred to as reliable and valid informants of quality of care. Empirical evidence has shown that nurse-reported quality of care is an indicator of hospital performance comparable to objective indicators of quality such as mortality and failure-to-rescue (McHugh and Stimpfel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Their perception of quality of care is not based on isolated contacts or adverse events, such as pressure ulcers or patient falls, but has developed over time in a variety of encounters with residents and in interdisciplinary collaboration. 5 Hospital studies showed that nurse-reported quality of care was related to mortality, failure to rescue, survival, and patients' reports of their care experience, 5e7 and was a valid indicator that reflected differences in hospital quality. 5 Based on the structure-process-outcome model of Donabedian,8 Figure 1 shows that quality of care, considered as an outcome is determined by structure and process factors, such as organizational, personnel, and resident characteristics, as well as the work environment, work stressors, and the necessity of rationing of care.…”
mentioning
confidence: 99%
“…5 Hospital studies showed that nurse-reported quality of care was related to mortality, failure to rescue, survival, and patients' reports of their care experience, 5e7 and was a valid indicator that reflected differences in hospital quality. 5 Based on the structure-process-outcome model of Donabedian,8 Figure 1 shows that quality of care, considered as an outcome is determined by structure and process factors, such as organizational, personnel, and resident characteristics, as well as the work environment, work stressors, and the necessity of rationing of care. The relationships of staffing level, turnover, or staff mix with quality of care have been broadly researched in nursing homes 9e11 with a tendency for better quality of care being associated with better staffing factors, but results are still inconclusive.…”
mentioning
confidence: 99%
“…The application of the nursing process enabled the team to cope successfully with the difficulties derived from old and new workloads and assimilate the different characteristics of work in the central services, where it is necessary to work efficiently and with due quality in the care of our indirect clients [37]. As these clients are usually inpatients or outpatients who receive the preparations prepared by us, we have attained a new focus on the care of our direct clients and for whom we have set up the Nursing Care Process: the nurses in the various hospital units and hospital services.…”
Section: Discussionmentioning
confidence: 99%